Laser‐aided curing of a GnP/epoxy nanocomposite optimised by multiscale finite element analysis. Issue 3 (30th January 2019) - Manta, Asimina; Soutis, Constantinos; Gresil, Matthieu
Abstract: In this work, the possibility of laser‐aided curing of graphene nanoplatelet (GnP)/epoxy nanocomposites is explored by means of finite element analysis. A multiscale and multiphysics analysis is performed to identify and optimise critical manufacturing parameters—laser speed and power. The proposed model is parametrically studied, and its results are thoroughly discussed in terms of polymerisation degree and temperature field depth. Finally, the laser scanning of a specimen was conducted, and the polymerisation performance was recorded.